The Effect of Al and Cu Electrode Configurations on the Thermoelectric Performance of PVA/glycerin/H3PO4-Based Ionic Thermoelectric Cells - Robiandi, Fadli; Shoodiqin, Dian Mart; Mayantasari, Menasita (Department of Physics Education, Universitas Mataram, 2025)
Ionic thermoelectric (i-TE) materials have the potential to be applied to devices for converting low-temperature heat energy into electricity. In this study, an I-TE cell made of PVA/glycerin/H3PO4 was synthesized using Al and Cu electrodes. The general objective of this study is to investigate how symmetrical electrode configurations (Al-Al, Cu-Cu) and asymmetrical configurations (Al-Cu) affect the thermoelectric performance of PVA/glycerin/H₃PO₄ polymer electrolyte cells, including potential difference, Seebeck coefficient, and power factor. The results of this study show that the PVA/glycerin/H₃PO₄ sample with asymmetric electrodes produces a higher potential difference than the sample with symmetric electrodes. The highest potential difference in the sample with asymmetric electrodes is 0.97 V. Meanwhile, the highest potential difference produced by the sample with symmetrical Al electrodes was 0.15 V. However, the highest increase in potential difference with respect to temperature gradient was observed in the PVA/glycerin sample with symmetrical Al electrodes. This was based on the Seebeck coefficient value produced by the sample, which was 16 mV/K. This is followed by the sample with an asymmetric electrode, and the lowest is the sample with a symmetric Cu electrode. The power factor of the sample increases with increasing temperature and follows the pattern of increasing ionic conductivity. In addition, the power factor is also influenced by the Seebeck coefficient value of the sample. In this study, samples with symmetrical Al electrodes showed the highest PF values, with a maximum value at a temperature of 65 °C. These findings indicate that polymer electrolyte cells based on PVA/glycerin/H₃PO₄ with Al and Cu electrodes have the potential for use in i-TE devices to convert low-quality thermal energy into electricity.